RECENT REDAGOGICAL STRATEGIES DIRECTED TOWARDS THE MAINTENANCE OF NATIONAL IDENTITY - Tvaltvadze, Darejan; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Today’s global processes foster the rapid internationalization and integration of educational systems of different countries. Globally-oriented strategies are spread all over Europe. They gradually “creep” into the state structures and set up new goals before the educational systems of developing countries. On the background of the ongoing internationalizing processes the question of the maintenance of national identity acquires an outstanding importance. State universities make an attempt to play a significant role in the solution of this problem. The given paper presents the latest pedagogical strategies implemented at the Faculty of Humanities of Ivane Javakhishvili Tbilisi State University. The major emphasis is put on the involvement of two ongoing projects into the university studies (“English-Georgian Encyclopedic Dictionary”, “The Georgian National Corpus”) and students’ participation in their further development. The given projects directly answer the demands of the modern epoch. On the one hand, they reveal western-oriented strategies via the introduction of the major concepts of today’s lingva franca. On the other hand, they serve as the tool of the maintenance of the national identity via the enrichment of the Georgian language and popularization of the Georgian literary monuments or manuscript sources among the foreigners. The strategies highlighted in the paper directly answer the following demand of the Council of Europe: “The rich heritage of diverse languages and cultures in Europe is a valuable common resource to be protected and developed”. Moreover, they can serve as an exemplary and useful model for those universities of developing countries, which strive towards the European integration and at the same time, facilitate the maintenance of the national identity.